Embedding health literacy research and best practice within a socioeconomically and culturally diverse health service: A narrative case study and revised model of co‐creation. (29th November 2022) - Muscat, Danielle M.; Mouwad, Dana; McCaffery, Kirsten; Zachariah, Dipti; Tunchon, Lyn; Ayre, Julie; Nutbeam, Don
Abstract: Background: Health literacy interventions and research outcomes are not routinely or systematically implemented within healthcare systems. Co‐creation with stakeholders is a potential vehicle through which to accelerate and scale up the implementation of innovation from research. Methods: This narrative case study describes an example of the application of a co‐creation approach to improve health literacy in an Australian public health system that provides hospital and community health services to one million people from socioeconomically and culturally diverse backgrounds. We provide a detailed overview of the value co‐creation stages and strategies used to build a practical and sustainable working relationship between a University‐based academic research group and the local health district focussed on improving health literacy. Results: Insights from our experience over a 5‐year period informed the development of a revised model of co‐creation. The model incorporates a practical focus on the structural enablers of co‐creation, including the development of a Community of Practice, co‐created strategic direction and shared management systems. The model also includes a spectrum of partnership modalities (spanning relationship‐building, partnering and co‐creating), acknowledging the evolving nature of research partnerships and reinforcing the flexibility and commitment required to achieve meaningful co‐creation in research. Four key facilitators of health literacy co‐creation are identified: (i) local champions, (ii) co‐generated resources, (iii) evolving capability and understanding and (iv) increasing trust and partnership synergy. Conclusion: Our case study and co‐creation model provide insights into mechanisms to create effective and collaborative ways of working in health literacy which may be transferable to other health fields in Australia and beyond. Patient and Public Contribution: Our co‐creation approach brought together a community of practice of consumers, healthcare professionals and researchers as equal partners.